2022
DOI: 10.3389/fmed.2022.812653
|View full text |Cite
|
Sign up to set email alerts
|

Solamargine Alleviated UVB-Induced Inflammation and Melanogenesis in Human Keratinocytes and Melanocytes via the p38 MAPK Signaling Pathway, a Promising Agent for Post-inflammatory Hyperpigmentation

Abstract: Post-inflammatory hyperpigmentation (PIH) is a common acquired pigmentary disorder occurring after skin inflammation or injury. Ultraviolet B irradiation could exaggerate PIH clinically due to its effect on promoting cutaneous inflammation and melanogenesis in keratinocytes and melanocytes, respectively. Solamargine (SM), a steroidal alkaloid glycoside extracted from Solanum undatum, significantly inhibits Ultraviolet B (UVB)-induced pro-inflammatory cytokines IL-1α, IL-1β, IL-8, and IFN-γ, as well as paracrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Solamargine (SM, Solanum undatum ), a triglycoside derivative of solasodine, has shown promising anti-inflammatory properties, especially in UVB-induced inflammation models [ 82 ]. SM at doses of 1 µg/mL managed to reduce mRNA and protein expression of several pro-inflammatory markers in HaCaT cells, namely Il-1α, IL-1β, IFNγ and IL-8.…”
Section: Therapeutic Context— Solanum S(g)asmentioning
confidence: 99%
“…Solamargine (SM, Solanum undatum ), a triglycoside derivative of solasodine, has shown promising anti-inflammatory properties, especially in UVB-induced inflammation models [ 82 ]. SM at doses of 1 µg/mL managed to reduce mRNA and protein expression of several pro-inflammatory markers in HaCaT cells, namely Il-1α, IL-1β, IFNγ and IL-8.…”
Section: Therapeutic Context— Solanum S(g)asmentioning
confidence: 99%
“…Finally, melanogenesis (pigmentation) is a vital adaptive protective response against further DNA damage induced by UVR (Nguyen et al , 2019). Upon UVB exposure, KC-derived paracrine factors (e.g., α-MSH) can control melanogenesis and affect the survival and the differentiation of MC vi Mitf, which is regulated by MAPK signaling (Juemin et al , 2022). Our previous work also showed that KC exerted a paracrine protective effect on UVB-mediated DNA damage, apoptosis and inflammatory responses in association with MAPK pathways in MC (Jeayeng et al , 2017).…”
Section: Introductionmentioning
confidence: 99%